Editorial Notes - Mhd Sarif, Suhaimi; Abdul Wahid, Nur Kamariah (IIUM Journal of Case Studies in Management, 2025)
This issue presents a compelling collection of case studies that integrate the timeless principles of Tawhidic epistemology and the holistic values of MADANI—Sustainability, Prosperity, Innovation, Respect, Trust, and Compassion. By bridging ethical innovation with the realities of modern business and societal challenges, these cases offer profound insights into leadership, strategic management, and value-driven decision-making in a rapidly evolving global landscape.